The Reflection of Critical Pedagogy on the Educational System: A Study among Teachers - Hilal Büyükgöze; Leyla Yılmaz Fındık (Elementary Education Online, 2023)
The current paper primarily aims to investigate teachers’ attitude toward critical pedagogy principles. The second aim of the study is to figure out whether participant teachers’ attitudes differ significantly in relation to their gender, school level, years of experience, membership to an educational union, and level of education. The study group consists of 199 females and 166 males with a total of 365 teachers. Data was collected from teachers working in primary and secondary education schools located in Ankara during the spring term of 2014/2015 academic year. The data collection tool was ‘Critical Pedagogy Principles Scale’ developed by Yılmaz (2009). The reliability of the instrument was examined by Cronbach’s alpha value, and construct validity of the scale was tested by confirmatory factor analysis. Data was analyzed by t test, ANOVA, Cohen’s d value (δ), eta squared (η2) and omega squared values (Ω2). Findings demonstrated that female teachers agreed on the critical pedagogy principles more than their male colleagues, and teachers with graduate degrees showed more positive attitude toward critical pedagogy principles than teachers with undergraduate degrees. It was also found that teachers’ attitude differ in the function of education dimension in relation to their years of experience, membership to a union, and school level. Results were assessed, and discussed within the related literature.